And Labor Came to Us: Making Use of an Opportune Workforce—Enhancing Migrant Integration into British Economy. (March 2018) - Hack-Polay, Dieu; Mendy, John
This article considers the opportunities presented by the availability of migrant labor in the U.K. employment market and its utilization. The research found that despite their qualifications, migrant labor is underutilized, thereby resulting in a readily available workforce being shunned and excluded from participative integration. This raises economic and ethical questions whose exploration revealed structural barriers (individually, communally, and institutionally) that impeded migrants' fulfillment of citizenship obligations to host communities and U.K. businesses. The article's key contribution is to highlight a skills mismatch and the persistent absence of institutional, communal, and strategic frameworks to support migrants' integration.